Alfabetização geográfica e as categorias de análise do espaço geográfico: uma proposta metodológica para os educandos do 6º ano do ensino fundamental - Saldanha, Cibele Stefanno (2024)
This research is based on the problem related to the difficulty students have in reading the categories of analysis of geographic space, namely: place, landscape, territory and region. Considering that geographic literacy begins in the 6th grade of the final years of Elementary School, including education for children and adolescents aged 11 and 12, it is necessary to consider the complexity of abstracting these concepts and, therefore, the geography teacher must seek to go beyond traditional classes. In this sense, the general objective of the research proposes a methodology to assist in geographic literacy based on these categories of analysis of geographic space, involving students in the 6th grade of Elementary School at Colégio Betta, in the city of Foz do Iguaçu, PR. To achieve the general objective, the following specific objectives were defined: (a) To identify how 6th grade students are assimilating the categories of geographic analysis and to verify their weaknesses; (b) Teach classes illustrating theoretical content by developing activities with images from different periods, observing the transformations that have occurred in space over time; (c) Examine students' perceptions through drawings they have created, tasks and questionnaires they have completed; (d) Evaluate possible advances in students' reading and interpretation of geographic space, in assimilating the proposed categories of analysis. In order to achieve the objectives, a qualitative analysis was adopted based on the deductive method and the systemic approach. A bibliographic review was carried out and then field research was carried out with students in the 6th grade of Colégio Betta. After analyzing the textbook adopted by Colégio Betta, a semi-structured interview was conducted with the teacher who teaches geography classes at this school. Next, classes were given in which the categories of analysis of geographic space were presented and activities using satellite images were developed. It was concluded that the use of images was widely accepted by students, provided a variety of information and contributed to geographic literacy. It was also observed that the textbook is insufficient for the students to assimilate the topic of categories of analysis of geographic space. Therefore, it is necessary to consider the use of other strategies to understand the concepts of these categories of analysis.